2020
DOI: 10.1177/0886260520959630
|View full text |Cite
|
Sign up to set email alerts
|

“Prevention Alone Is Not Enough:” Stakeholders’ Perspectives About School-based Child Sexual Abuse (CSA) Prevention Programs and CSA Research in China

Abstract: While existing studies have examined the effectiveness of school-based child sexual abuse (CSA) prevention programs in China, there is currently little qualitative evidence on how stakeholders view these programs and research on CSA in China more generally. To address this research gap, the aims of this study were to explore stakeholders’ perspectives on: (a) school-based CSA prevention programs in China; (b) the components of these programs; (c) CSA research in China. Qualitative semi-structured interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, some studies have shown that specific sexual abuse prevention knowledge and skills (e.g., rejection skills) do not differ significantly from the control group after participation in a program (Chen et al, 2019). Few studies have examined the overall effects of school-based CSA prevention education in China (Lu et al, 2020), so it remains unclear what kinds of program content and formal design can have the greatest positive impact on children. Therefore, it is necessary to explore the effectiveness of current school-based CSA prevention programs in China.…”
Section: School-based Csa Prevention Education Programsmentioning
confidence: 99%
“…However, some studies have shown that specific sexual abuse prevention knowledge and skills (e.g., rejection skills) do not differ significantly from the control group after participation in a program (Chen et al, 2019). Few studies have examined the overall effects of school-based CSA prevention education in China (Lu et al, 2020), so it remains unclear what kinds of program content and formal design can have the greatest positive impact on children. Therefore, it is necessary to explore the effectiveness of current school-based CSA prevention programs in China.…”
Section: School-based Csa Prevention Education Programsmentioning
confidence: 99%
“…While schools are deemed to be one of the most promising institution for the delivery of CSA prevention and response efforts due to their consistent and longitudinal contact with children and their families ( Lu et al, 2022 ), school closures in disruptive occurrences like the COVID-19 pandemic make it necessary to look for alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we generated our initial program theory by examining studies in two recent systematic reviews on this topic (i.e. Walsh et al, 2015; Lu et al, in preparation). We addressed problems related to this approach at the theory refinement stage where we systematically searched for studies with a range of types of research designs.…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al, 2017), there is a paucity of evidence regarding the underpinning context and mechanisms that contribute to the intended outcomes. A recent qualitative study (Lu et al, 2020) questioned the effectiveness of such programs given the lack of infrastructure services for children who disclose CSA in China, indicating the need to explore how contextual factors and underlying mechanisms impact intervention efficacy and uptake.…”
Section: Introductionmentioning
confidence: 99%